2015
DOI: 10.1200/jco.2015.33.3_suppl.402
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemoradiation therapy for cholangiocarcinoma to improve R0 resection rate: The first report of phase II study.

Abstract: 402 Background: With the much-improved surgical techniques of hepatic lobectomy, but the long-term survival of patients undergoing such surgery remains far from satisfactory. Then, to improve the prognosis of cholangiocarcinoma patients, we have applied neoadjuvant chemoradiation therapy followed by conventional resection for possibly resectable cholangiocarcinoma, named NACRAC. Here, we analyzed and evaluated the Phase II (P-2) study. Methods: Patients with histologically or cytologically confirmed adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Several additional retrospective studies demonstrated neoadjuvant CRT can successfully convert patients with unresectable to resectable disease and with a high R0 rate (Table 2). 25,31‐33 Meta‐analyses of these studies were done by neoadjuvant regimen. The random‐effects model suggests an overall R0 resection rate 0.81 (95% CI: 0.54, 0.94).…”
Section: Extrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…Several additional retrospective studies demonstrated neoadjuvant CRT can successfully convert patients with unresectable to resectable disease and with a high R0 rate (Table 2). 25,31‐33 Meta‐analyses of these studies were done by neoadjuvant regimen. The random‐effects model suggests an overall R0 resection rate 0.81 (95% CI: 0.54, 0.94).…”
Section: Extrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…In the NACRAC phase I study, gemcitabine 600 mg/m 2 (days 1 and 8) for two cycles every 3 weeks plus 45 Gy of radiation therapy was reported as the recommended preoperative regimen for biliary tract cancer [35]. In NACRAC phase II study, 25 patients received the above-mentioned neoadjuvant chemoradiation and 17 patients achieved R0 resection (70.8%) [36]. The longterm follow-up data have not been published yet.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%
“…[22][23][24][25] Recently, studies on neoadjuvant therapy have been conducted as a bridge modality to improve the rate of radical resection of locally advanced hilar cholangiocarcinoma. [26][27][28] In view of these trends, especially those from 2000, the impact of surgical skills and methods remains important; however, the perioperative support and management are also thought to contribute to the oncological outcomes in patients with hilar cholangiocarcinoma.…”
Section: 16mentioning
confidence: 99%